Mathematica navigator : mathematics, statistics, and graphics - Ruskeepää, Heikki (Elsevier/Academic Press, 2009)
Ruskeepaa gives a general introduction to the most recent versions of Mathematica, the symbolic computation software from Wolfram. The book emphasizes graphics, methods of applied mathematics and statistics, and programming. Mathematica Navigator can be used both as a tutorial and as a handbook. While no previous experience with Mathematica is required, most chapters also include advanced material, so that the book will be a valuable resource for both beginners and experienced users. - Covers both Mathematica 6 and Mathematica 7 - The book, fully revised and updated, is based on Mathematica 6 - The CD-ROM contains material about the new properties of Mathematica 7 - With the CD-ROM, the entire book and the material about Mathematica 7 can be installed into the help system of Mathematica - Comprehensive coverage from basic, introductory information through to more advanced topics - Studies several real data sets (included in the CD-ROM) and many classical mathematical models.